1998
DOI: 10.1001/archpsyc.55.12.1121
|View full text |Cite
|
Sign up to set email alerts
|

Treating Major Depression in Primary Care Practice

Abstract: The Depression Guideline Panel of the Agency for Health Care Policy and Research in 1993 published recommendations for treating major depression in primary care practice that were often based on studies of tertiary care psychiatric patients. We reviewed reports of randomized controlled trials in primary care settings published between 1992 and 1998. This evidence indicates that both antidepressant pharmacotherapy and time-limited depression-targeted psychotherapies are efficacious when transferred from psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
206
1
7

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 449 publications
(223 citation statements)
references
References 65 publications
9
206
1
7
Order By: Relevance
“…For example, although encouraged by the investigators not to do so, study PCPs may have discussed our treatment advice with each other. Still, the recovery rate of UC patients was similar to that experienced by the UC cohort in a report from Schulberg et al 47 Patients may also have seen a PCP on the date of the PRIME-MD who was not their usual PCP, may have switched providers within the group practice, or may have seen another PCP, who had been randomized to a different study condition, when their own PCP was unavailable (e.g., on vacation). However, we found that just 8% of study patients saw a PCP other than their usual provider on the date of the PRIME-MD's administration, and switching PCPs while remaining within the group practice was uncommon (<10%).…”
Section: Discussionsupporting
confidence: 66%
“…For example, although encouraged by the investigators not to do so, study PCPs may have discussed our treatment advice with each other. Still, the recovery rate of UC patients was similar to that experienced by the UC cohort in a report from Schulberg et al 47 Patients may also have seen a PCP on the date of the PRIME-MD who was not their usual PCP, may have switched providers within the group practice, or may have seen another PCP, who had been randomized to a different study condition, when their own PCP was unavailable (e.g., on vacation). However, we found that just 8% of study patients saw a PCP other than their usual provider on the date of the PRIME-MD's administration, and switching PCPs while remaining within the group practice was uncommon (<10%).…”
Section: Discussionsupporting
confidence: 66%
“…The resulting treatment, however, was not sufficient to affect clinical outcomes. In contrast with results of these scree-ning interventions, programs of screening followed by systematic treatment have been clearly demonstrated to improve patient outcomes (Schulberg et al, 1996;Katzelnick et al, 2000). We conclude that increasing recognition of depression is a necessary, but not sufficient, step .toward providing effective depression treatment in primary care.…”
Section: The Challenges Of Implementationmentioning
confidence: 78%
“…In a randomized trial among US urban primary care patients, Schulberg et al (1996) found that manual-based Interpersonal Psychotherapy was clearly superior to Epidemiologia e Psichiatria Sociale, 9, 3, 2000 usual primary care. In the Edinburgh Primary Care Depression Study, clinical improvement during cognitive therapy was similar to that seen in specialty trials (Scott & Freeman, 1992).…”
Section: The Effectiveness Of Treatmentmentioning
confidence: 99%
See 2 more Smart Citations